Question and Answers Forum

All Questions      Topic List

Differential Equation Questions

Previous in All Question      Next in All Question      

Previous in Differential Equation      Next in Differential Equation      

Question Number 93815 by i jagooll last updated on 15/May/20

(D^2 +6D+9)y = (e^(−3x) /x^3 )

(D2+6D+9)y=e3xx3

Answered by john santu last updated on 15/May/20

homogenous solution  λ^2 +6λ+9=0  λ = −3,−3   y_h  = Ae^(−3x) +Bxe^(−3x )   particular solution  (D+3)[ (D+3)(e^(3x) )]=(1/x^3 )  (D+3)[D(e^(3x) y)] = (1/x^3 )   (D+3)(e^(3x) y)=∫ (1/x^3 ) dx=−(1/(2x^2 ))  e^(3x) y = ∫ −(1/(2x^2 )) dx =  y_p  = (1/(2x.e^(3x) )) = (e^(−3x) /(2x))  generall solution  y = Ae^(−3x) +Bxe^(−3x) +(e^(−3x) /(2x))

homogenoussolutionλ2+6λ+9=0λ=3,3yh=Ae3x+Bxe3xparticularsolution(D+3)[(D+3)(e3x)]=1x3(D+3)[D(e3xy)]=1x3(D+3)(e3xy)=1x3dx=12x2e3xy=12x2dx=yp=12x.e3x=e3x2xgenerallsolutiony=Ae3x+Bxe3x+e3x2x

Commented by i jagooll last updated on 15/May/20

thAnk you

thAnkyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com